Epidermal defect nevi. Nevi of dermis and subcutaneous fat. Clinically silent nevus. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2002)
Before talking about defect epidermal nevi, we would like to emphasize that their pathogenetic mechanisms are more complex than those ones of excess nevi, because mutations and monoclonal cell proliferations are not responsible for these defect nevi. The concept of defect nevus was underlined with regard to hypopigmented nevus, which is the counterpart of hyperpigmented nevus. Hypopigmented nevus has been already discussed (Eur. J. Pediat. Dermatol. 10, 145-54, 2000). (...).